DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman - Khalaji-Pirbalouty, Valiallah; Raupach, Michael J. (Zootaxa, 2016)
Two species of Atarbolana (Cirolanidae: Isopoda) from the intertidal zone of the Gulf of Oman and the Persian Gulf were studied and redescribed. The known distribution of this small genus is limited to the northern areas of the Indian Ocean, from the Pakistan coasts to the Persian Gulf. The analyses of DNA barcodes as well as detailed morphological studies clearly support the existence of three distinct Atarbolana species along the coastal zone of the Persian Gulf and northern Arabian Sea. Furthermore, A. dasycolus Yasmeen, 2004 is synonymized with A. setosa Javed and Yasmeen, 1989.